2018
DOI: 10.1007/s00330-018-5738-y
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular characteristics of lower-grade diffuse gliomas: investigating vessel size imaging for differentiating grades and subtypes

Abstract: ObjectivesVessel size imaging (VSI) could reveal average microvessel diameter. The aim was to investigate microvascular characteristics and the efficacy of VSI in lower-grade glioma (LGG) grading and subtype differentiation based on 2016 classification of central nervous system tumours.MethodsFifty-seven LGG (grade II/III, 36/21) patients who received VSI examination before surgery were retrospectively analysed. The average (Rmean) and maximum (Rmax) vessel size indexes were obtained. The long (VDmax) and shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Finally, the rate transfer coefficient (K ep ) can be used to reflect the reflux rate of the contrast agent via the changes in signal intensity of the contrast agent over time in the blood vessels and extravascular spaces (13,14). These MRI features are closely associated with the histological classification and metabolic process of glioma (15,16), which can reflect the molecular characteristics (17) and genotype (18) of this tumor type, and thus provide a reliable basis for individualized diagnosis and treatment (19).…”
Section: Patient-derived Orthotopic Xenograft Glioma Models Fail To Rmentioning
confidence: 99%
“…Finally, the rate transfer coefficient (K ep ) can be used to reflect the reflux rate of the contrast agent via the changes in signal intensity of the contrast agent over time in the blood vessels and extravascular spaces (13,14). These MRI features are closely associated with the histological classification and metabolic process of glioma (15,16), which can reflect the molecular characteristics (17) and genotype (18) of this tumor type, and thus provide a reliable basis for individualized diagnosis and treatment (19).…”
Section: Patient-derived Orthotopic Xenograft Glioma Models Fail To Rmentioning
confidence: 99%
“…Genes that influence vascular biology, such as VEGF and TGF-β2, are highly expressed in IDH wild type tumors [25]. As a result, these tumors are more angiogenic, show greater cerebral blood volume, higher permeability, and alterations in pericyte and endothelial cell function in comparison to their IDH mutant counterparts [26]. While cerebral vessel disease affects brain structural connectivity [16], it remains to be proven that the vascular phenotype of IDH wild type gliomas contribute to disrupted connectivity differently than that of the mutant variant.…”
Section: Discussionmentioning
confidence: 99%
“…This study is an extension of a previously reported work. 12,13 This study was performed in accordance with the ethical standards of the 1964 Declaration of Helsinki and its most recent amendments.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%